A Preliminary X-ray Study of Murine Tnfaip8/Oxi-α - Lee, Daeun (Molecular Diversity Preservation International (MDPI), 2014)
Tnfaip8/oxidative stress regulated gene-α (Oxi-α) is a novel protein expressed specifically in brain dopaminergic neurons and its over-expression has been reported to protect dopaminergic cells against OS-induced cell death. In this study, murine C165S mutant Tnfaip8/Oxi-α has been crystallized and X-ray data have been collected to 1.8 Å using synchrotron radiation. The crystal belonged to the primitive orthorhombic space group P2(1)2(1)2, with unit-cell parameters a = 66.9, b = 72.3, c = 93.5 Å. A full structural determination is under way in order to provide insights into the structure-function relationships of this protein.